a+2s=3(s-2)+1

Simple and best practice solution for a+2s=3(s-2)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+2s=3(s-2)+1 equation:


Simplifying
a + 2s = 3(s + -2) + 1

Reorder the terms:
a + 2s = 3(-2 + s) + 1
a + 2s = (-2 * 3 + s * 3) + 1
a + 2s = (-6 + 3s) + 1

Reorder the terms:
a + 2s = -6 + 1 + 3s

Combine like terms: -6 + 1 = -5
a + 2s = -5 + 3s

Solving
a + 2s = -5 + 3s

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2s' to each side of the equation.
a + 2s + -2s = -5 + 3s + -2s

Combine like terms: 2s + -2s = 0
a + 0 = -5 + 3s + -2s
a = -5 + 3s + -2s

Combine like terms: 3s + -2s = 1s
a = -5 + 1s

Simplifying
a = -5 + 1s

See similar equations:

| x^2+17x-193=0 | | t=x^2+3x | | 2a^2+23a+45=0 | | 8(-38x+32)=-43(-21+8x) | | 10(x+1)-4v=3(2v+3)-11 | | 3n-4=2n | | 1.1x-1.62=-1.4 | | 3x+7=7-(4x-9) | | 5.75+5-k= | | x=t^2+3t | | 800x=100x^2 | | 2(5x+3)=98+3x | | 9(8z+9)+6=-273 | | -6(x-7)-7=-7x+2 | | -2.5--0.7=x | | 1.1x=3y-0.4 | | 3p+3.7=9.1 | | -13=x+72 | | n-5=-13 | | .2(x+3)-.5(x+3)=-0.3-0.9 | | 496=62x | | 3/8c=6 | | (n-7)-2n=12 | | 10-2(x+10)=60 | | 7x-1=23+7x | | x+4.07=6.46 | | 6x+6=11-2x | | 8x-15=155 | | -b+8=-15 | | 7s=-49 | | R+(R-12)=90 | | 5x-15=155 |

Equations solver categories